2020
DOI: 10.1016/j.celrep.2020.107815
|View full text |Cite
|
Sign up to set email alerts
|

CD28 Regulates Metabolic Fitness for Long-Lived Plasma Cell Survival

Abstract: SUMMARY Durable humoral immunity against epidemic infectious disease requires the survival of long-lived plasma cells (LLPCs). LLPC longevity is dependent on metabolic programs distinct from short-lived plasma cells (SLPCs); however, the mechanistic basis for this difference is unclear. We have previously shown that CD28, the prototypic T cell costimulatory receptor, is expressed on both LLPCs and SLPCs but is essential only for LLPC survival. Here we show that CD28 transduces pro-survival signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…A recent report found that differential expression of Lcp2, which encodes the CD28 adaptor protein SLP76, linked CD28 signaling in LLPCs to increased Irf4 expression and an IRF4-mediated increase in mitochondrial mass and oxidative phosphorylation. This increase in metabolic fitness was proposed as a mechanism for LLPC survival in the bone marrow niche (Utley, Chavel et al, 2020). However, a previous study failed to identify Lcp2 as differentially expressed between ASCs and follicular B cells (Shi et al, 2015) and our own RNA-seq analysis showed no significant difference in Lcp2 expression between TG PCs and WT PCs.…”
Section: Crtc2 Regulates Mature B Cell Mrna Transcription and Splicingmentioning
confidence: 63%
See 1 more Smart Citation
“…A recent report found that differential expression of Lcp2, which encodes the CD28 adaptor protein SLP76, linked CD28 signaling in LLPCs to increased Irf4 expression and an IRF4-mediated increase in mitochondrial mass and oxidative phosphorylation. This increase in metabolic fitness was proposed as a mechanism for LLPC survival in the bone marrow niche (Utley, Chavel et al, 2020). However, a previous study failed to identify Lcp2 as differentially expressed between ASCs and follicular B cells (Shi et al, 2015) and our own RNA-seq analysis showed no significant difference in Lcp2 expression between TG PCs and WT PCs.…”
Section: Crtc2 Regulates Mature B Cell Mrna Transcription and Splicingmentioning
confidence: 63%
“…The metabolism of LLPCs differs from SLPCs (Lam et al, 2016, Utley et al, 2020, although the mechanism(s) underlying differences in lifespan remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that signaling through the CD28 PYAP ICD is required for enhanced glycolysis in T cells activated for 24 hours 46 . Earlier studies found that PI3K activation by CD28 induced GLUT1 expression and enhanced glycolysis over the same 24 hour activation period 3,47 , indicating that the signaling initiated by the membrane proximal YMNM and membrane distal PYAP domains of CD28 cooperate to induce glycolytic metabolism during T cell priming.…”
Section: Discussionmentioning
confidence: 99%
“…These are the long-lived PC (LLPC). In contrast to their SL brothers, LLPCs secrete much higher amounts of Ab and can live for decades inside the BM, where they migrate without dividing [ 52 , 53 ].…”
Section: Physiologic B Lymphopoiesismentioning
confidence: 99%